Design and Implementation of a Social CRM-Based Website Framework for Enhanced Information Services - Ibrahim, Ali; Oklilas, Ahmad Fali; Novianti, Hardini (Informatika, Universitas Jenderal Soedirman, 2025)
The development of website technology has encouraged digital transformation in various sectors, especially in the provision of information services. The website not only acts as a medium for delivering information, but also as a means of interaction between service providers and users. However, there are still many institutions that have not optimized the potential of the website to the fullest to build sustainable relationships with users. The result of this research is the design of a Social CRM-Based Website Framework for Enhanced Information Services. The Social CRM model enables two-way interaction, real-time feedback monitoring, and digital community management that supports openness and active user participation. The application of this model is directed at optimizing information services through improving the quality of communication, responsiveness, and personalization of content based on user needs. The results show that the majority of users want a website that is easy to access, informative, and integrated with social media, especially Facebook. The number of respondents in this study was 150 respondents, and the application of the Quicksort Algorithm for data analysis. This study proposes a Social CRM-based website framework to enhance user engagement in academic information services. Using the User-Centered Design (UCD) method, the system was developed and evaluated through a System Usability Scale (SUS) with 106 users. The results showed a usability score of 72 (Good). Integration with Facebook showed positive engagement, although data privacy concerns were noted.